Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review - Page 474: 56


The solutions are $\frac{-1}{5}$ and -3.

Work Step by Step

4(5x+1)(x+3)=0 5x+1=0 or x+3=0 5x+1-1=0 -1 or x+3-3=0-3 5x= -1 or x=-3 x=$\frac{-1}{5}$ The solutions are $\frac{-1}{5}$ and -3. Check Let x=-3 4(5x+1)(x+3)=0 4[5(-3)+1](-3+3)=0 4[5(-3)+1]0=0 0=0 Let x=$\frac{-1}{5}$ 4(5x+1)(x+3)=0 4[5*$\frac{-1}{5}$+1](-1+3)=0 4(-1+1)2=0 4*0*2=0 0=0
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.